Meta-analysis of the prevalence of arterial hypertension in Kazakhstan - Suleimenova, Yerke; Kuanyshbekov, Yerzhan; Abdullayev, Arslan; Akhmadyar, Nurzhamal; Karibayeva, Indira (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Arterial hypertension is a major global health concern and a leading risk factor for cardiovascular diseases, stroke, and kidney failure. The prevalence of hypertension continues to rise due to sedentary lifestyles, urbanization, and aging populations. In Kazakhstan, hypertension represents a growing burden, with an estimated 3.8 million affected adults and low control rates. This systematic review and meta-analysis assessed the prevalence of arterial hypertension in Kazakhstan by synthesizing data from observational studies. Methods: A systematic literature search was conducted across PubMed, Scopus, ScienceDirect, Web of Science, and Google Scholar. Studies were selected based on predefined inclusion and exclusion criteria. Data extraction followed PRISMA guidelines. The Newcastle–Ottawa Scale (NOS) was used to evaluate the quality. Meta-analysis was performed to calculate the pooled estimates with heterogeneity assessed through evaluation and meta regression. Results: Out of 335 titles assessed a total of five studies met the inclusion criteria, involving 4,716 participants from multiple regions of Kazakhstan. The pooled prevalence of arterial hypertension was 27% (95% CI: 20–34%), with significant heterogeneity (I² = 99%). Meta-regression suggested that sample size was not a significant predictor of prevalence variability. Studies varied in terms of study design, population characteristics, and diagnostic criteria. Conclusions: This review revealed high prevalence of hypertension in Kazakhstan. Targeted public health interventions, enhanced primary care, and improved data collection are essential to reduce disease burden. Emphasizing health education, regional policy planning, and digital health tools will support better hypertension control across the country.